Decision Support System For The Selection Of The Best Extension Officers Applying The Method Of Additive Ratio Assessment (Case Study: Department Of Agriculture Deli Serdang) - Hotni Rotua Br Hutapea (STMIK Budi Darma, 2019)
Agricultural extension workers are agents of change directly related to farmers. The selection of instructors so far that takes place at the Deli Serdang Agriculture Office takes a very long process, based on the problem, a decision support system (SPK) is needed that can facilitate the selection of the best instructors by using existing criteria. One method used is Additive Ratio Assessment (ARAS). The ARAS method is able to solve problems in decision making with alternatives and criteria that have been given weight. Research using ARAS ranks the lowest extension to the highest ranking. The best instructor selection system was built using Microsoft Visual Studio 2008 and MySQL as a database.